2007
DOI: 10.1532/ijh97.07012
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Survey of Hemophagocytic Lymphohistiocytosis in Japan

Abstract: Hemophagocytic lymphohistiocytosis (HLH), a disorder of the mononuclear phagocyte system, can be classified into two distinct forms: primary HLH (FHL) and secondary HLH. To clarify the epidemiology and clinical outcome for each HLH subtype, we conducted a nationwide survey of HLH in Japan. Since 799 patients were diagnosed in 292 institutions of Japan between 2001 and 2005, the annual incidence of HLH was estimated as 1 in 800,000 per year. Among them, 567 cases were actually analyzed in this study. The most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
335
2
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(361 citation statements)
references
References 36 publications
14
335
2
10
Order By: Relevance
“…Secondary HLH is associated with a variety of infections, autoimmune diseases and malignancies. Epstein-Barr virus (EBV)-associated HLH (EBV-HLH) is the most frequent subtype of HLH in Japan [4]. Establishing a diagnosis of HLH may be difficult when based solely on clinical and laboratory findings, because those findings are often present in severely ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary HLH is associated with a variety of infections, autoimmune diseases and malignancies. Epstein-Barr virus (EBV)-associated HLH (EBV-HLH) is the most frequent subtype of HLH in Japan [4]. Establishing a diagnosis of HLH may be difficult when based solely on clinical and laboratory findings, because those findings are often present in severely ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although HLH is extremely rare in Western areas of the world, it is common in Asia. In Japan, the annual incidence of HLH was estimated as 1 in 800,000 per year (primarily the acquired form) [3]. HLH was the most common in NK/ T cell lymphoma (i.e., up to 24.7 %) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, survival has been shown to be dependent on the type of lymphoma. Indeed, B cell lymphoma has been reported to be much more favorable than T-NK cell lymphoma [3]. Machaczka [15] examined eight patients and found that only one patient with HLH-04 who was treated with an allogeneic stem cell transplant survived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutations identified to date lead to abnormalities in the perforin cytotoxic pathway causing decreased function of NK-and/or cTC, indicating a pivotal role of this event in the pathogenesis of HLH [2]. Recently, there have been increasing reports of adult onset HLH in the context of conditions associated with immune dysregulation: hematologic malignancies, infections, autoimmune diseases, organ/ stem cell transplants and chemo-or immunosuppressive therapies [3][4][5][6][7]. Some of the cases affecting young adults represent attenuated familial forms of the disease due to partial loss of function of the HLH-causing genes [8], while in older adults (>60 yr.) malignancy associated HLH is most common.…”
Section: Commentarymentioning
confidence: 99%